2022
DOI: 10.1007/s12035-022-02757-y
|View full text |Cite
|
Sign up to set email alerts
|

lncRNA BDNF-AS Attenuates Propofol-Induced Apoptosis in HT22 Cells by Modulating the BDNF/TrkB Pathway

Abstract: Propofol is widely used as an intravenous anesthetic in clinical practice. Previous studies have indicated that propofol induces apoptosis in neurons. Brain-derived neurotrophic factor (BDNF), a neurotrophic factor, is associated with neuronal apoptosis. BDNF-AS, a relatively conserved long non-coding RNA, can reverse the transcription of BDNF. This study aimed to investigate the involvement of BDNF-AS in propofol-induced apoptosis in HT22 cells. HT22 cells were treated with various concentrations of propofol … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 28 publications
0
9
0
Order By: Relevance
“…41 microRNAs (miRNAs) and long noncoding RNAs (lncRNAs) have been found to be involved in the neurotoxicity process of propofol. 42,43 MicroRNAs (miRNAs) are endogenous noncoding RNA molecules with a length of approximately 22 nucleotides that regulate cellular processes by inhibiting the translation of messenger RNAs. 44 MiRNAs have become a research hotspot on the neurotoxicity of anesthetics in recent years.…”
Section: Noncoding Rnamentioning
confidence: 99%
“…41 microRNAs (miRNAs) and long noncoding RNAs (lncRNAs) have been found to be involved in the neurotoxicity process of propofol. 42,43 MicroRNAs (miRNAs) are endogenous noncoding RNA molecules with a length of approximately 22 nucleotides that regulate cellular processes by inhibiting the translation of messenger RNAs. 44 MiRNAs have become a research hotspot on the neurotoxicity of anesthetics in recent years.…”
Section: Noncoding Rnamentioning
confidence: 99%
“…Uncleaved proBDNF preferentially binds to p75 neurotrophin receptor (p75NTR), whereas mature BDNF may preferentially bind to tyrosine kinase receptor B (TrkB). , Uncleaved proBDNF binds to the p75NTR and activates RhoA, a small GTPase that regulates actin cytoskeleton polymerization, resulting in inhibition of axonal elongation, growth cone collapse, and apoptosis. A previous study demonstrated that propofol exposure to developing neurons isolated from DIV 4–7 BALB/c mice induces apoptosis through the p75NTR/RhoA/RhoA kinase (ROCK) pathway . In addition, another study found that propofol exposure suppresses mature BDNF protein expression in a dose- and time-dependent manner and increases apoptosis of HT22 mouse hippocampal neuronal cells by inhibiting the BDNF/TrkB pathway …”
Section: Mechanisms Of Propofol-induced Developmental Neurotoxicitymentioning
confidence: 99%
“…78 In addition, another study found that propofol exposure suppresses mature BDNF protein expression in a dose-and time-dependent manner and increases apoptosis of HT22 mouse hippocampal neuronal cells by inhibiting the BDNF/TrkB pathway. 79 BDNF can be almost secreted by astrocytes in a paracrine fashion. 80 Astrocytes, the largest population of glial cells, powerfully control the formation, maturation, function, and elimination of synapses through various secreted and contactmediated signals.…”
Section: Structural and Functional Damage Of Mitochondriamentioning
confidence: 99%
“…Both FGF2 and BDNF have natural antisense transcripts, RNA molecules that are transcribed from the opposite strand of protein‐coding genes, and are suggested to regulate the transcription of their sense strand (Modarresi et al., 2012). Supporting this, BDNF‐antisense is reported to be a discordant regulator of BDNF protein expression, such that, when BDNF‐antisense levels increase, BDNF protein expression decreases (Xu et al., 2022). A similar role was suggested for FGF‐antisense (FGF‐AS) in the regulation of FGF2 expression based on initial in vitro studies (Baguma‐Nibasheka et al., 2007, 2012; Li & Murphy, 2000; MacFarlane et al., 2010); however, several other in vitro studies failed to detect an interaction between FGF‐AS and FGF2 expression levels (Asa et al., 2001; Baguma‐Nibasheka et al., 2005, 2012; MacFarlane et al., 2010).…”
Section: Introductionmentioning
confidence: 95%